Dismissal from employment and the remedies - Ali Mohamed, Ashgar Ali (LexisNexis, 2007)
Dismissal from employment and the remedies is basically intended to provide a clear understanding that surrounds the concept of a worker's 'security of tenure' in employment with reference to common law and statutory law. It elaborates the remedies of workers at common law wrongful dismissal and statutory unfair dismissal in further bringing to light the concept of 'security of tenure' in employment. It also contains a general discussion of the types and the various grounds that may constitute a justifiable ground to dismiss a workman from employment. In addition, this book describes the few hurdles a workman has togo through before his representation under section 20(1) of the Industrial Relations Act 1967 may be referred to and adjudicated in the Industrial Court, i.e. reinstatement, and further, has highlighted the drawbacks of monetary compensation and called for legislative guidelines of its assessment. Further, the book also contains the discussion of the present system of judicial review in the civil High Court and the much sought after Industrial Appeal Court process. It also contains the mode of enforcement of awards of the Industrial Courts and some references to Islamic Law on the following subject matters: the concept of work, duty of the employee to discharge trust, employer's obligation to protect a worker's dignity, sexual harrassment and drug abuse in the workplace. This book could be of interest to Human Resource officers, undergraduate and postgraduate students of universities, academicians, and the general public.